The effect of PTZ-induced epileptic seizures on hippocampal expression of PSA-NCAM in offspring born to kindled rats - Rajabzadeh, Aliakbar (BioMed Central, 2012)
BACKGROUND: Maternal epileptic seizures during pregnancy can affect the hippocampal neurons in the offspring. The polysialylated neural cell adhesion molecule (PSA-NCAM), which is expressed in the developing central nervous system, may play important roles in neuronal migration, synaptogenesis, and axonal outgrowth. This study was designed to assess the effects of kindling either with or without maternal seizures on hippocampal PSA-NCAM expression in rat offspring. METHODS: Forty timed-pregnant Wistar rats were divided into four groups: A) Kind(+)/Seiz(+), pregnant kindled (induced two weeks prior to pregnancy) rats that received repeated intraperitoneal (i.p.) pentylenetetrazol, PTZ injections on gestational days (GD) 14-19; B) Kind(-)/Seiz(+), pregnant non-kindled rats that received PTZ injections on GD14-GD19; C) Kind(+)/Seiz(-), pregnant kindled rats that did not receive any PTZ injections; and D) Kind(-)/Seiz(-), the sham controls. Following birth, the pups were sacrificed on PD1 and PD14, and PSA-NCAM expression and localization in neonates’ hippocampi were analyzed by Western blots and immunohistochemistry. RESULTS: Our data show a significant down regulation of hippocampal PSA-NCAM expression in the offspring of Kind(+)/Seiz(+) (p = 0.001) and Kind(-)/Seiz(+) (p = 0.001) groups compared to the sham control group. The PSA-NCAM immunoreactivity was markedly decreased in all parts of the hippocampus, especially in the CA3 region, in Kind(+)/Seiz(+) (p = 0.007) and Kind(-)/Seiz(+) (p = 0.007) group’s newborns on both PD1 and 14. CONCLUSION: Our findings demonstrate that maternal seizures but not kindling influence the expression of PSA-NCAM in the offspring’s hippocampi, which may be considered as a factor for learning/memory and cognitive impairments reported in children born to epileptic mothers.